Preparation method and application of composite porous carbon
By using composite porous carbon preparation methods, the mixed porous carbon gas gel derived from hierarchical waste bread is used to prepare APC-RGO/CNP hybrid gas gel composite materials for the electrodes used for supercapacitors to solve the existing super capacitor The problems of stability and electrochemical performance under high stress conditions have realized efficient energy density and power density, and are suitable for multi -functional pressure sensing devices.
Patent Information
- Application Number
- CN202410976074.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-19
AI Technical Summary
Existing supercapacitors are prone to leakage of liquid electrolytes and release of dangerous by-products under high stress and large deformation conditions, and their electrochemical properties are mainly concentrated in the unloading state, so their performance under different loads is less studied.
Adopt composite porous carbon preparation methods, produce a hybrid polynol carbon gas gel derived from scald/activated technology to produce hierarchical bread derived, synthesize APC-RGO/CNP hybrid gas gel composite materials for the electrodes of supercapacitors to enhance their mechanics to enhance their mechanics Performance and electrochemical performance.
The stability and safety of the supercapacitors under high stress conditions have been realized, and their electrochemical properties are improved under different loads. Sensing device.
Smart Images

Figure CN118908210B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous carbon preparation, and in particular to a preparation method and application of composite porous carbon. Background Art
[0002] With the development of science and technology, a new generation of environmentally friendly and sustainable electronic products is urgently needed to meet the increasing needs of "food" and "energy" problems in the future. In recent years, biomass materials extracted from plants, food and animals have attracted much attention due to their functional programmability, cost-effectiveness and eco-friendliness. Active biomass materials (such as sugarcane, loofah and watermelon) have been widely studied due to their properties of storing and transferring electrons and ions in energy storage devices such as supercapacitors. Compared with active biomass materials with one-dimensional and planar structures, biomass porous carbon, as a three-dimensional conductive skeleton, has the advantages of excellent porosity, specific surface area and chemical stability, and has an important position and broad development prospects in the fields of wearable energy storage and sensing devices.
[0003] Supercapacitors (SCs) as an energy storage device have attracted extensive attention due to their excellent power density and long cycle life. In particular, great attention has been paid to the development of power systems that can maintain stable and excellent electrochemical performance. To achieve this goal, attention should be paid to the design and optimization of electrodes and electrolytes to meet the growing energy demand. Recent studies have focused on the application of biomass-derived porous carbon materials in supercapacitor electrodes because of their unique macroporous structure and interconnected conductive network, which can facilitate the diffusion and transport of electrolyte ions. This use of porous materials not only greatly improves the safety of the device but also reduces the weight of the device. In addition, most of the synthesized porous carbon materials have a microporous structure and a high specific surface area. For example, SCs with graphite-like porous carbon electrodes show ideal capacitive characteristics and flexibility, with a charge transfer rate of 0.1A g -1 The specific capacitance at the current density is 258.5 F g -1 In another study, SCs composed of MOFs-derived asymmetric porous carbon materials were used at 250 W kg -1 The energy density is 32.90Wh kg -1 Furthermore, scalable methods are needed to improve the stability and specific capacity of active biomass materials.
[0004] In practical applications, SCs are always exposed to complex environments, which can lead to leakage of liquid electrolytes and release of hazardous byproducts even under high stress and large deformation conditions. Gel electrolytes have become increasingly popular as a potential supercapacitor device due to their multiple capabilities, which can be regarded as electrolyte separators, adhesives, and sensors. However, for commercial SCs, gel electrolytes face many challenges, including leakage, filling, and corrosion. In addition, damage to the electrode material and the electrolyte / electrode interface can cause supercapacitors to fail under external loads, and its failure mechanism is still unclear. Therefore, the issue of safety under high stress needs to be considered in the actual use of the device. However, the electrochemical performance of SCs is mainly concentrated in the unloaded state, and previous works have rarely studied the electrochemical performance of SCs under different loads. In addition, due to the influence of mechanical properties, non-flexible electrochemical energy storage devices are usually applied to a limited range of uses, limiting their practical multifunctional applications.
[0005] In general, SCs with both excellent electrochemical and mechanical properties are rarely explored. Therefore, it is necessary to propose a preparation method and application of composite porous carbon to solve the above problems. Summary of the invention
[0006] The present invention aims at the problem of how to prepare SCs with excellent electrochemical and mechanical properties, and proposes a method for preparing composite porous carbon.
[0007] The preparation method of the composite porous carbon comprises the following steps:
[0008] S1. Preparation of active porous carbon APC:
[0009] S1.1, carbonizing the dried bread in argon at 600°C to obtain bread carbon material;
[0010] S1.2, immerse 600 mg of bread carbon material in 50 mL of 1 mol / L KOH solution for 10 min, and then keep the bread carbon material sample treated with KOH in argon at 600 ° C for 1 hour to obtain APC material;
[0011] S1.3. Thoroughly wash the APC material with deionized water to remove residual chemicals;
[0012] S2. Synthesis of APC-rGO and APC-rGO / CNP composites:
[0013] S2.1, immersing the prepared APC block into 50 mL of 5 mg / mL graphene oxide GO dispersion;
[0014] S2.2, the APC coated with GO dispersion was kept in a drying oven at 60°C for 4 hours to obtain APC-GO, and its mass after complete drying was about 300 mg;
[0015] S2.3, synthesis of APC-rGO composite material: 100 mg of ascorbic acid was mixed in 50 mL of deionized water by stirring to obtain a mixed solution 1; then, the APC-GO material was immersed in the mixed solution 1 for 2 hours, and this process resulted in the reduction of APC-GO to obtain about 260 mg of APC-rGO composite material;
[0016] S2.4. Synthesis of APC-rGO / CNP composite material: The APC-GO composite material was placed in a mixed solution II including 300 mg 1,4-phenylenediboric acid and 20 mL methanol to obtain a mixture; then, the mixture was placed in a 50 mL Teflon reactor and the temperature was set to 90°C. After 24 hours, the APC surface reacted to generate graphene oxide framework film APC-GOFs. Then, the APC-GOFs was washed with methanol several times; 100 mg ascorbic acid was mixed in 50 mL deionized water by stirring to obtain a mixed solution III; then, the APC-GOFs material was immersed in the mixed solution III for 2 hours. This process resulted in the reduction of APC-GOFs; finally, an APC-rGO / CNP composite material with a total mass of approximately 400 mg was obtained.
[0017] In a preferred embodiment of the present invention, the bread in S1.1 is ordinary bread made from flour, and the bread is carbonized in argon for 3 hours.
[0018] Furthermore, the size of the APC block in S2.1 is 1 cm×1 cm×2 cm.
[0019] In a preferred embodiment of the present invention, the APC-rGO / CNP composite material has a specific capacitance of 474.8 F / g, a conductivity of 3.23 S / cm, and a compression modulus of 124.60 MPa at a current density of 1.0 A / g.
[0020] Furthermore, the APC-rGO / CNP composites were used to assemble symmetrical solid-state APC-rGO / CNP / / APC-rGO / CNP supercapacitors with a power density of 895 W kg -1 When the energy density is 17.4Wh·kg -1 , and the maximum power density is 4680Wkg -1 .
[0021] Implementing the embodiments of the present invention has the following beneficial effects:
[0022] The preparation method of the composite porous carbon of the present invention produces a hierarchical waste bread-derived hybrid porous carbon aerogel with excellent conductivity and high compression modulus through a calcination / activation process. The obtained APC-rGO / CNP hybrid aerogel composite material can be used as an SCs electrode. The symmetrical APC-rGO / CNP / / APC-rGO / CNP device is fabricated as a compressible electrochemical capacitor, which has a high conductivity at 822.8 W / kg even under a large stress level of 20 kPa. -1 The energy density is 25.6Wh kg -1 , the capacitance retention rate is 93.8% in 10,000 cycles;
[0023] In addition, the APC-rGO / CNP composite also exhibited significant elastic electrochemical stress sensing capability with a stress sensitivity of about 0.22 kPa. -1 The APC-rGO / CNP porous carbon composite material has strong mechanical properties, high conductivity, significant pressure sensing and energy storage properties, and has potential application prospects in the field of wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 Schematic diagram of the synthesis of APC-rGO / CNP porous carbon materials through carbonization, activation and reduction processes;
[0026] Figure 2 (a)-(c) are SEM images of APC, (d)-(f) are SEM images of APC-rGO, and (g)-(i) are SEM images of APC-rGO / CNP; (j)-(k) are TEM images, (l) is HRTEM image and its inset is the selected area electron diffraction (SAED) pattern of APC-rGO / CNP;
[0027] Figure 3(a) is the XRD spectra of (1) APC, (2) APC-GO, (3) APC-rGO and (4) APC-rGO / CNP samples, (b) is the Raman spectra of (1)-(4) samples, (c) is the N2 adsorption and desorption isotherms of APC, APC-rGO and APC-rGO / CNP samples; (d) is the pore size distribution corresponding to APC, APC-rGO and APC-rGO / CNP samples, (e)-(h) are the XPS spectra of (1) APC, (3) APC-rGO and (4) APC-rGO / CNP samples;
[0028] Figure 4 (a) is the scanning rate of 20mV s -1 CV curves of APC, APC-rGO and APC-rGO / CNP electrodes at a current density of 1.0A. -1 (c) is the GCD curve at a scan rate of 1 mV s -1 -100mV s -1 (d) is the CV curve and (e) is the Nyquist plot of APC-rGO / CNP based on the GCD curve of the electrode at different current densities, (f) is the specific capacitance of APC-rGO / CNP based on the GCD curve at different current densities and the CV curve at different scan rates;
[0029] Figure 5 In a three-electrode system, the current density is 2Ag -1 Cyclic stability test when
[0030] Figure 6 (a) at a scan rate of 1.0 mV s -1 CV curves of APC rGO / CNP / / APC rGO / CNP SSC in different scanning voltage windows, electrochemical performance of APC-rGO / CNP in a two-electrode system with (PVA / KOH) gel electrolyte: (b) CV curves of SSC at 0-1.8 V and (c) GCD curves, (d) Ragone plot of SSC device;
[0031] Figure 7 (a) Schematic diagram of the structure of SSC under different pressures (0 kPa, 10 kPa and 50 kPa), (b) CV curves (20 mV s -1 ) and (c) GCD curve (1.0Ag -1 ), (d) capacitance and cycle performance under high stress 20 kPa, (e) EIS curve and (f) magnified image of SSC under 0-50 kPa load;
[0032] Figure 8 (I) A gasket (1×1 cm) with negligible mass was placed between the weight and the SSC contact area. 2 ), stress is equal to the applied force divided by the contact area; (II) is the capacitance sensing test of the supercapacitor: (a) initial state, and under different stress loading conditions: (b) 1 kPa, (c) 2 kPa, (d) 5 kPa, (e) 10 kPa, (f) 20 kPa, (g) 50 kPa, (h) no load;
[0033] Fig. 9 (a) is the inverse of the square root of the specific capacitance (C) and the scan rate (v -1 / 2 ), (b) is a comparison of the capacitance contribution of the double layer and pseudocapacitance of APC, APC-rGO, and APC-rGO / CNP, and (c) is a graph of 10 mV s -1 (d) is the capacitance contribution of APC-rGO / CNP at different scan rates, and (e) is the capacitance contribution of APC, APC-rGO and APC-rGO / CNP at 10 mV s -1 -100mV s -1 The peak current density and scan rate under the condition follow a power law (i = av b ), (f) is the change of b value of APC-rGO / CNP / / APC-rGO / CNP SSC with stress (0-50 kPa), the inset shows ... -1 -100mV s -1 Power law relationship curve of peak current density within the scan rate range.
[0034] Fig.10 Compression performance test of PVA / KOH gel electrolyte after freeze / thaw treatment: (a) initial state and different weight loading: (b) 10 kPa, (c) 50 kPa, (d) no loading, (e) Nyquist plot of gel electrolyte during compression;
[0035] Fig.11 for Fig.10 Supplement of the compression performance test of PVA / KOH gel electrolyte under different loads: (a) initial state and different weight loading conditions, (b) 1 kPa, (c) 2 kPa, (d) 5 kPa, (e) 10 kPa, (f) 20 kPa, (g) 50 kPa, (h) unloading;
[0036] Fig.12(a) is the conductivity comparison between (1) APC, (2) APC-rGO and (3) APC-rGO / CNP samples, (b) is the stress-strain curve comparison of (1)-(3) samples in experimental and numerical simulation conditions, (c) is the compression test picture of (1)-(3) samples, (d) is the curve of the relative resistance change rate of APC-rGO / CNP sample with strain change, (e) is the curve of the relative resistance change rate of APC-rGO / CNP sample with stress change, (f) is the cyclic test curve of APC-rGO / CNP under different stresses (displacements), (g) is the real-time resistance change rate of APC-rGO / CNP sensor when pressing and releasing on the keyboard, (h) is the change of resistivity with time when making a fist and releasing the fist;
[0037] Fig.13 The static cloud diagrams of the finite element simulation of three samples (columns): (a) APC, (b) APC-rGO and (c) APC-rGO / CNP under compression at different times (T1-T4, rows), Note: T1 (step time = 0) represents the initial moment, T2 (step time = 0.2118) represents the moment when the pore unit crack starts, T3 (step time = 0.9625) represents a time point in the crack propagation process, and T4 (step time = 1) represents the moment when the crack growth stops;
[0038] Fig.14 The finite element simulation displacement cloud diagrams corresponding to the three samples (a) APC, (b) APC-rGO and (c) APC-rGO / CNP (columns) at different times (T1-T4, rows) under compression conditions;
[0039] Fig.15 STATUSXFEM images of APC, APC-rGO and APC-rGO / CNP at time points T1-T4;
[0040] Fig.16 (a) Images of APC-rGO / CNP samples connected by wires under different compressive deformations: (b) initial state, (c) continuous loading state, (d) fracture failure state, (e) initial state and (f) deformation state of irregular porous structure under loading conditions;
[0041] Fig.17 This is the relationship curve between the relative resistance change rate and strain of the APC-rGO / CNP sample. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The preparation method of the composite porous carbon comprises the following steps:
[0044] 1. Preparation of active porous carbon APC:
[0045] 1. Carbonize the dried bread in argon at 600°C for 3 hours to obtain bread carbon material; the bread is ordinary bread made from flour.
[0046] 2. Immerse 600 mg of bread carbon material in 50 mL of 1 mol / L KOH solution for 10 min, and then keep the bread carbon material sample treated with KOH in argon at 600 ° C for 1 hour to obtain APC material;
[0047] 3. Rinse the APC material thoroughly with deionized water to remove residual chemicals.
[0048] 2. Synthesis of APC-rGO and APC-rGO / CNP composites:
[0049] 1. Immerse the prepared APC block (size 1 cm × 1 cm × 2 cm) in 50 mL of 5 mg / mL graphene oxide GO dispersion;
[0050] 2. Keep the APC coated with GO dispersion in a drying oven at 60°C for 4 hours to obtain APC-GO, which has a mass of about 300 mg after complete drying;
[0051] See also Figure 1 , Figure 1 Schematic diagram of the synthesis of APC-rGO / CNP porous carbon materials through carbonization, activation and reduction processes:
[0052] 3. Synthesis of APC-rGO composites: Figure 1 As shown in a, 100 mg of ascorbic acid was mixed in 50 mL of deionized water by stirring to obtain a mixed solution 1; then, the APC-GO material was immersed in the mixed solution 1 for 2 hours. This process resulted in the reduction of APC-GO, and about 260 mg of APC-rGO composite material was obtained;
[0053] 4. Synthesis of APC-rGO / CNP composite material: The APC-GO composite material was placed in a mixed solution II including 300 mg 1,4-phenylenediboronic acid and 20 mL methanol to obtain a mixture; then, the mixture was placed in a 50 mL Teflon reactor and the temperature was set to 90°C. After 24 hours, the APC surface was reacted to generate a graphene oxide framework film APC-GOFs. Then, the APC-GOFs were washed with methanol several times; 100 mg ascorbic acid was mixed in 50 mL deionized water by stirring to obtain a mixed solution III; then, the APC-GOFs material was immersed in the mixed solution III for 2 hours. This process resulted in the reduction of the APC-GOFs; finally, the following was obtained: Figure 1 b shows the APC-rGO / CNP composite material with a total mass of approximately 400 mg.
[0054] For characterization of the composite materials prepared by the above method, see Figure 2 :
[0055] The morphology of the composites was studied by scanning electron microscopy:
[0056] The morphologies of APC, APC-rGO and APC-rGO / CNP composites were observed using scanning electron microscopy. Figure 2 The SEM image of ac shows that pure APC has an irregular porous structure, with a smooth pore skeleton surface and sharp edges; Figure 2 The APC-rGO in df has obvious macropores and a structure interconnected by the coated wrinkled rGO film; in addition, Figure 2 The images in gi show that the morphology of the APC-rGO / CNP composite material has changed significantly compared with that of APC-rGO, and the surface has transformed into non-uniformly distributed spherical carbon nanoparticles.
[0057] Transmission electron microscopy characterization of composite materials:
[0058] Figure 2 j confirmed that the rGO coating consisted of graphene sheets with wrinkled morphology, indicating that the GO sheets split into several layers and were reduced to rGO; Figure 2 k shows carbon nanoparticles covered on the surface of two-dimensional ultrathin rGO sheets (~6 layers).
[0059] High-resolution transmission electron microscopy characterization of composite materials:
[0060] Figure 2 l is Figure 2 The magnified image of the red rectangular box in k shows that amorphous carbon can be observed near the lattice fringes of rGO from the high-resolution transmission electron microscopy (HRTEM) image, where the distance between the (002) planes is about 0.34 nm; Figure 2 The image on the upper left side corresponds to the SAED pattern, where two diffuse rings are observed, further illustrating the presence of an amorphous structure, corresponding to the (002) and (100) crystal planes, respectively, illustrating the polycrystalline and low crystallinity in APC rGO / CNP.
[0061] Please participate in the following representations Figure 3 :
[0062] XRD spectrometer was used to characterize the phase with Cu-Ka (k=0.154056 nm) (BrukerAXS Co.):
[0063] The structures of APC, APC-GO, APC-rGO and APC-rGO / CNP samples were studied by XRD analysis. Figure 3 a) Two broad peaks are shown near diffraction angles of 26.4° and 42.5°, corresponding to the (002) and (100) crystal planes of graphitic carbon materials. For the APC-GO sample, a sharp diffraction peak is observed at 11.4°, corresponding to the (001) crystal plane of GO, and its spacing is calculated to be 0.76nm using the Bragg equation. In addition, a broad diffraction peak is observed at 26.3°, indicating the coexistence of GO and APC. As the sharp peak of GO disappears, the APC-GO sample is reduced by ascorbic acid, indicating the synthesis of APC-rGO. In addition, after the hydrothermal and reduction reaction of graphene and carbon nanoparticles to form rGO / CNP composites, the peak at ~26.3° becomes weaker and broader, indicating that APC-rGO / CNP has a lower average degree of graphitization.
[0064] Raman spectroscopy was performed using a microprobe (inVia, Renishaw Instruments):
[0065] Figure 3 b shows the peaks of (1) APC, (2) APC-GO, (3) APC-rGO and (4) APC-rGO / CNP at 500 cm -1 -2500cm -1 The Raman spectrum of graphite carbon is located at 1344cm -1 (D peak) and 1582cm -1 The (G peak) indicates that the graphene film wrinkles and pore edges cause the carbon layer stacking. In the Raman spectrum of APC, the D peak (1344 cm -1 ) and G peak (1589cm -1) show two obvious Raman peaks, respectively, with an ID / IG value of about 0.98, the ID / IG value of the APC-GO sample composed of APC and GO is 0.91, and the ID / IG value of APC-rGO is 1.03, which is better than APC-GO, indicating that APC-GO is reduced by ascorbic acid, which leads to a reduction of oxygen-containing functional groups in GO nanosheets. In addition, when ascorbic acid is used as a reducing agent to reduce APC and GOFs to prepare APC-rGO / CNP composites, the ID:IG ratio can reach 1.15, indicating that the conjugated graphene / carbon network is reestablished due to the disordered structure and defects of amorphous carbon.
[0066] The samples were studied by Brunner-Emmet-Teller (BET) measurements in N2 adsorption / desorption at 77.3 K using Quantachrome Instruments (NOVA2000e):
[0067] exist Figure 3 In Figure 3, the nitrogen adsorption isotherms of APC, APC-rGO, and APC-rGO / CNP exhibit type IV isotherms with obvious hysteresis loops, indicating a porous structure. The gaps between graphene sheets and a large number of carbon nanoparticles enrich the porous structure and increase its specific surface area (SSA). The SSA values of APC, APC-rGO, and APC-rGO / CNP are 1150 m 2 g -1 、1207m 2 g -1 and 1532m 2 g -1 Compared with APC, APC-rGO / CNP has the highest SSA, which can be attributed to the wrinkled morphology of rGO layers and the voids between rGO sheets and carbon nanoparticles.
[0068] Perform Barrett–Joyner–Halenda (BJH) analysis:
[0069] The results are as follows Figure 3 As shown in (d), the inset in the range of 0-10 nm shows that the surface pore distribution provided by APC is mainly mesopores and macropores, which indicates its potential for extensive electrolyte preservation and reduced diffusion distance. Meanwhile, with the increase in the volume of micropores and mesopores of APC-rGO and APC-rGO / CNP, the morphology of APC-rGO / CNP samples confirms a three-dimensional hierarchical porous structure composed of macropores, mesopores and micropores.
[0070] X-ray photoelectron spectroscopy (XPS) was performed using an ESCALAB250Xi (Thermo Fisher Scientific).
[0071] XPS measurement spectra can be used to estimate C, N, and O elements. Figure 3 e shows two prominent peaks at 284.7eV and 532.5eV, corresponding to the peaks of C1s and O1s, respectively, but the nitrogen peak of the functional group amino group of bread is not clearly visible. Figure 3 f, the peaks centered at ca 284.5 eV, 285.2 eV, and 286.1 eV correspond to C=C (sp 2 carbon atom), CC / N(sp 3 It is estimated that the C contents in APC, APC-rGO, and APC-rGO / CNP are 92.1%, 92.8%, and 93.4%, respectively. Figure 3 g reveals the changes in the nitrogen N1s peaks of APC, APC-rGO and APC-rGO / CNP samples, which contain four separate peaks, including pyridinic nitrogen (N-6, 398.3 eV), pyrrolic nitrogen (N-5, 399.7 eV), graphitic nitrogen (NQ, 400.6 eV) and pyridinic nitrogen (NO, 403.2 eV). The concentrations of NQ and N-6 are significantly higher than those of N-5 and NO, and the NO concentration of samples (1)-(4) gradually decreases. In particular, the nitrogen content in APC is approximately 2.8%, while in APC-rGO / CNP this value remains at 0.3%, indicating that the reduction reaction of APC and GOFs by ascorbic acid easily leads to the breakage of CC / N bonds. Figure 3 h, for the O1s fitting peak, the spectrum can be fitted to C=O quinone group (530.7 eV), COC ether group and / or C-OH phenol group (532.1 eV), ester group (-OC=O) (533.0 eV) and chemically adsorbed oxygen (-COOH carboxyl group, 534.8 eV). In addition, when APC is modified by rGO and rGO / CNP films, the concentration of chemically adsorbed oxygen at 534.8 eV is significantly increased. Compared with the ester group in APC-rGO, APC-rGO / CNP has a relatively higher content (0.65%), which is attributed to the esterification reaction between B14DBA molecules and graphene oxide. The organic functional groups of rGO nanosheets and / or the carbides of B14DBA can be introduced into APC-rGO / CNP. Furthermore, after the addition of ascorbic acid, the COC and / or C-OH groups centered at ca.532.1 eV are reduced, which can not only enrich the lattice defects and disordered structure but also improve the wettability of carbon materials, which is beneficial to enhance the conductivity and surface wettability of electrode materials.
[0072] For studies on the electrochemical properties of electrodes, see Figure 4 :
[0073] Figure 4 a and b show the current density of 1.0 A g-1 When APC, APC-rGO and APC-rGO / CNP electrodes were at 20 mV s -1 CV curves and GCD curves at scan rates. According to the XPS energy spectrum, due to the doping of N and O, all CV curves are rectangular, showing the characteristics of double-layer capacitance (EDLC) and pseudocapacitance (PC). The improvement of APC-rGO / CNP specific capacitance is attributed to the irregular carbon nanoparticles of different sizes on the rGO sheets, which provide a fast ion transfer pathway. Doping with N and O elements can introduce pseudocapacitive properties and enhance the wettability of the electrode, which also increases the accessibility of charge flow in the energy storage device. Therefore, the APC-rGO / CNP electrode at 1Ag -1 It shows excellent specific capacitance (474.8F g -1 ), exceeding Figure 4 a and APC (258.5F g -1 )、APC-rGO(353.6F g -1 ) and other carbon-based electrodes.
[0074] Figure 4 c and d show the CV curves of APC-rGO / CNP electrode at different scan rates and at 1, 2, 3, 4, 5 and 10 Ag. -1 The corresponding GCD curve under . In addition, by Figure 4 The electrochemical impedance spectroscopy (EIS) in e shows that the solution resistance R s , Charge transfer R ct , double layer capacitance C dl and Warburg resistance W. R ct (semicircle) and R s (real axis intercept) are 0.90Ω and 0.94Ω respectively. -1 Up to 10Ag -1 and the scan rate was from 1mV s -1 Increase to 20mV s -1 The specific capacitance ( Figure 4 f), the rate performance was found to be very good.
[0075] Also, see Figure 5 The cycling stability of the APC-rGO / CNP electrode was tested in a three-electrode system. -1 At a constant current density of 1.3 Å, the specific capacitance value remained at 98.6% of the original value after 10,000 charge / discharge cycles, indicating that the APC-rGO / CNP electrode has excellent cycling stability.
[0076] Table 1 Comparison of specific capacitance of APC, APC-rGO and APC-rGO / CNP in three-electrode system
[0077]
[0078]
[0079] See also Figure 6 To determine the optimal operating voltage range, the 1mV s -1 The cyclic voltammogram (CV) of APC-rGO / CNP / / APC-rGO / CNP symmetric supercapacitor (SSC) at a scan rate of Figure 6 As shown in a, there is no obvious polarization phenomenon at 1.8 V, indicating that the optimal voltage range is between 0 and 1.8 V. Therefore, SSC at 1.0 Ag -1 The specific capacitance can reach 155F g -1 ( Figure 6 b and c), while at 5.0Ag -1 and 10.0Ag -1 The specific capacitances are 84.5 F g -1 and 41.4F g -1 .exist Figure 6 d, the device is at 895W·kg -1 The energy density provided is 17.4Wh·kg -1 At the same time, when the energy density is 7.8Wh·kg -1 The maximum power density reached 4680W·kg -1 This result is superior to previously reported carbon and / or graphene-based supercapacitors such as NFHPCs / / NFHPCs supercapacitors (power density of 380.94 W kg -1 The energy density reaches 12.91Wh·kg -1 ), NCs / / NCs supercapacitors (at 700W·kg -1 When the temperature reaches 15.2Wh·kg -1 )、AMT-B-Fe / / AMT-B-Fe supercapacitor (at 300W·kg -1 When the temperature reaches 11.67Wh·kg -1 )PG-C / / PG-C(at 375W·kg -1 When the temperature reaches 9.38Wh·kg -1 ), Ti3C2T x / rGO-4 / / Ti3C2T x / rGO-4 symmetric supercapacitor (at 500W·kg -1 7.5Wh·kg -1), Gel / G-1.0 / / Gel / G-1.0 symmetric supercapacitor (at 50.03 W·kg -1 When reaching 6.39Wh·kg -1 ), NCGs / / NCGs symmetric supercapacitor (at 447W·kg -1 When the temperature reaches 12.7Wh·kg -1 ), N-doped C / rGO / / N-doped C / rGO symmetric supercapacitor (at 400 W·kg -1 When reaching 14.6Wh·kg -1 ), BNCs / / BNCs symmetrical supercapacitors (at 400W·kg -1 When reaching 9.33Wh·kg -1 ), NPC-700 / / NPC-700 symmetrical supercapacitor (at 85W kg -1 When reaching 18.8Wh·kg -1 ), CSHPGC / / CSHPGC symmetric supercapacitor (at 100W·kg -1 When the temperature reaches 10.2Wh·kg -1 ), oxide-doped HPC / / oxide-doped HPC symmetric supercapacitor (at 600 W kg -1 Reach 17.7Wh·kg -1 ) and supercapacitors based on UH-RH / PLGC=1 composite materials (at 150.85 W kg -1 When reaching 8.1Wh·kg -1 ).
[0080] See also Figure 7 and 8 , Figure 7 a and Figure 8 The responses of APC-rGO / CNP / / APC-rGO / CNP SSC under different quasi-static loads are shown. Figure 7 As shown in b, the CV curves of the supercapacitor change significantly in the pressure range of 0-50 kPa and the voltage range of 0-1.8 V, but at 20 mV s -1 It still maintains a rectangular shape, indicating that it has a sensitive current response to external stimuli. Figure 7 c shows 1.0Ag -1 It can be seen from the GCD curve under current density that the capacitance increases from 161.4F g -1 Increased to 227.8F g -1 As the stress increases from 1kPa to 20kPa ( Figure 7 d), under a compressive stress of 20 kPa, the energy density is as high as 25.6 W h kg -1, power density up to 822.8W kg -1 In addition, under a load of 20 kPa, APC-rGO / CNP / / APC-rGO / CNP SSC -1 After 10,000 cycles at a constant current, the capacity retention rate is still 93.8%. The EIS curve and magnified image of SSC under 0-50 kPa load are shown in Figure 2. Figure 7 e and f, the EIS data were fitted by the CNLS method, as shown in Table 2. In the high frequency range, as the applied pressure increases to 20 kPa, the semicircle shows a downward trend, that is, R ct From 6.69Ω to 1.69Ω, the corresponding R s The estimated value decreased from 3.87Ω to 1.98Ω, indicating that the interfacial charge transfer and effective ion diffusion between the electrode and the PVA / KOH gel electrolyte were enhanced, thereby increasing the capacitance value of the supercapacitor. However, when the stress reached 50kPa, the calculated R s and R ct They are 4.78Ω and 4.93Ω respectively. Figure 7 d, the capacitance is reduced to 137.6F g -1 , indicating that the polarization behavior at the double layer affects the electrochemical performance of the supercapacitor. When not loaded, the capacitance almost returns to the initial value, showing excellent mechanical stability and reversibility.
[0081] Table 2 Calculation results of EIS parameters of APC-rGO / CNP / / APC-rGO / CNP SSC under different applied pressures
[0082]
[0083] In order to further understand the contribution of double layer capacitance and pseudocapacitance to the total capacitance (C) of APC, APC-rGO and APC-rGO / CNP electrodes, the differential capacitance was calculated using the Trasatti method.
[0084] C=k1+k2v –1 / 2 (1)
[0085] In general, C is composed of a rate-dependent component k1 (contributing to the double-layer capacitance) and a diffusion-controlled component k2v that is limited by the scan rate. –1 / 2 (determine the contribution of PC), the double layer capacitor is calculated by calculating the APC, APC-rGO and APC-rGO / CNP electrodes with respect to v –1 / 2 The intercept k1 of the fitting curve is obtained ( Fig. 9 a). When the scan rate is changed from 1mV s –1 Rise to 10mV s –1 When C and (scan rate)-1 / 2 The relationship diagram shows a linear relationship, indicating that the pseudocapacitive behavior may exist in the slow diffusion region provided by the doped O and N elements. Fig. 9 b shows the APC, APC-rGO and APC-rGO / CNP electrodes at 10 mV s -1 The capacitance difference between APC-rGO and APC-rGO / CNP shows that the contribution value of the double-layer capacitor exceeds 90%, which is higher than 84.7% of APC. Fig. 9 As shown in Fig. 3, the contribution of the double-layer capacitance in APC-rGO / CNP is as high as 93.1%, and the remaining 6.9% of pseudocapacitance can be obtained by subtracting the double-layer capacitance from the total capacitance. Fig. 9 As shown in Figure d, the capacitance contribution at different scan rates further shows that PC gradually decays with increasing scan rate due to insufficient diffusion time. Through the relationship between current density (i) and scan rate (v), the following equation can be used to analyze the mixed characteristics of EDLC and PC for all electrodes:
[0086] i=av b (2)
[0087] log(i)=blog(v)+log(a) (3)
[0088] The b value can be determined by the slope of the log(i) vs. log(v) curve, where i is the peak current (A) and v is the scan rate (mV s -1 ), a and b are variable parameters. When b = 0.5, it mainly corresponds to slow reaction kinetics, while b = 1 mainly represents ultrafast reaction kinetics. Fig. 9 (e) It can be seen that APC, APC-rGO and APC-rGO / CNP electrodes have a high conductivity at 1 mV s -1 Up to 20mVs -1 The b values in the range are estimated to be 0.88, 0.90, and 0.94, respectively, indicating excellent ultrafast reaction kinetics. The remarkable electrochemical performance of APC-rGO / CNP is attributed to the high specific surface area of the porous APC material and the formation of more micropores and mesopores by the irregular carbon nanoparticles grown on the rGO film, which promotes fast ion transport, while the N and O atom doping introduces pseudocapacitance and enhances the wettability of the electrode. Fig. 9 (f) shows that the b-values of APC-rGO / CNP / / APC-rGO / CNP SSC under 0-50 kPa stress are in the range of 0.77-0.87. The inset shows the 10 mV s -1 -100mV s -1The power-law dependence of the peak current density at 20 kPa clearly indicates that the current response is mainly contributed by the EDLC in the 0-1.8 V operating voltage window. The results show that the initial b-value of the SSC (0.82) increases to 0.87 at 20 kPa, and decreases to 0.80 and 0.77 as the stress increases to 40 kPa and 50 kPa, respectively. The lower b-value in the larger stress region is mainly caused by the full contact of the electrode interface and the deformation of the freeze-thaw gel electrolyte. + The disordered transfer at the edge of the APC-rGO / CNP electrode and the random distribution of a small number of ions in the porous structure of APC resulted in a decrease in the reaction kinetics, which was enhanced after pressure release.
[0089] In order to further verify the effect of PVA / KOH gel electrolyte on the electrochemical performance of supercapacitors within the elastic limit range ( Fig.10 ad and Fig.11 ), Fig.10 e shows the Nyquist plot of the gel electrolyte under 0-50 kPa load. When the stress gradually increases to 20 kPa, the intercept between the curve and the real axis in the high-frequency region of the Nyquist plot reaches a minimum, indicating that the electrolyte in the porous APC-rGO / CNP electrode is saturated due to the release and embedding of the electrolyte. However, when the stress reaches 50 kPa, the distance between the electrodes is significantly reduced, which may accelerate the deformation and polarization of the gel electrolyte. In addition, the intercept increases and the slope of the linear part may decrease, resulting in an increase in diffusion impedance. After unloading, the capacitance remains at 156 F g -1 , which is 0.97% higher than that in the initial state, indicating that the porous electrode is in full contact with the gel electrolyte under low stress.
[0090] Sensing mechanism of APC-rGO / CNP composites based on channel cracks:
[0091] The changes in the structure and conductivity of the assembled pressure sensor device during compression are the key factors in the sensing mechanism. Fig.12 a shows the electrical properties of APC, APC-rGO and APC-rGO / CNP. In the APC-rGO / CNP sample, KOH-activated porous carbon, reduced graphene oxide and carbon nanoparticles constructed multiple conductive network channels between APC and rGO / CNP, which helped to improve the electrical conductivity. The APC-rGO / CNP bulk material exhibited a 3.23±0.55S cm -1 The conductivity is higher than that of APC (2.1±0.67S cm -1 ) and is much higher than that of APC-rGO sample (2.6±0.34S cm -1 ) conductivity.
[0092] In order to clarify the effects of pore structure and graphene / carbon coating on the mechanical properties of APC, APC-rGO and APC-rGO / CNP monolithic materials, mechanical properties tests were carried out, and the finite element method (FEM) was used to analyze the stress distribution, crack initiation and crack propagation at different time responses, e.g. Figure 13-15 The stress-strain curves obtained from the experiment and numerical simulation are compared. Fig.12 b shows the experimental values of the compressive strength of APC (2.06MPa), APC-rGO (2.41MPa) and APC-rGO / CNP (3.0MPa), corresponding to fracture strains of 2.85%, 2.37% and 2.57%, respectively. The Young's modulus values of APC, APC-rGO and APC-rGO / CNP porous carbon materials obtained experimentally are 83.50MPa, 100.23MPa and 124.60MPa, respectively, which are consistent with the simulation results in Table 3. Compared with other porous carbon composites, the current APC-rGO / CNP composite exhibits excellent mechanical properties and electrical conductivity ( Fig.12 c and Table 4). This is attributed to the synergistic effect between the interconnected conductive network formed by KOH activation and the rGO / CNP coating. Fig.12 As observed in Figure d, when the strain gradually increased to 2.85%, visible cracks appeared in the network structure of APC. As the stress continued to increase, these cracks (indicated by the red dashed line) extended upward along the porous skeleton, eventually leading to the fracture of the APC bulk material. In the APC-rGO sample, as the strain gradually increased to 2.37%, cracks began to form inside the porous APC and rGO coating, and the rGO coating on the outside of the porous skeleton also began to fall off. However, it was not until the compressive strain reached 2.57% that obvious cracks appeared on the APC-rGO / CNP, indicating that the rGO / CNP coating was able to adhere tightly to the APC surface and would not fall off. As the stress increased further, small cracks appeared in the APC-rGO / CNP, resulting in partial damage to the porous skeleton. Fig.16 ad show the APC-rGO / CNP samples connected to tin foil electrodes under different compressive deformations. As the lateral strain increases, the tin foil electrodes attached to the upper and lower parts of the bulk material are destroyed. Fig.16 ef is the initial state and deformation state of the irregular porous structure under loading conditions, indicating that during the continuous loading stage (>1000 kPa), stress concentration and cracks are prone to occur at the edges of the macroscopic pores, leading to bending, deformation and fracture of the porous carbon material.
[0093] Table 3 Comparison of equivalent mechanical performance parameters of three samples between numerical simulation and experimental measurement
[0094]
[0095] Note: The experimental value is abbreviated as “E” and the numerical simulation value is abbreviated as “S”.
[0096] Table 4 Comparison of mechanical properties and electrical conductivity of different porous carbon composites
[0097]
[0098]
[0099] Piezoresistive properties of APC-rGO / CNP sensor based on channel cracks:
[0100] In order to further improve the sensing performance of APC-rGO / CNP porous materials, the resistance change during uniaxial compression was monitored in real time. Sensitivity is a value that evaluates the ability of a material to convert pressure into an electrical signal. For strain sensors, sensitivity is usually measured by the gauge factor (GF):
[0101]
[0102] For pressure sensors, sensitivity (S) is defined as follows:
[0103]
[0104] where R0 is the initial resistance, ΔR is the resistance change of the APC-rGO / CNP sample, ε represents the tensile strain, and ΔP is the pressure change.
[0105] See also Fig.17 , Fig.17 The relationship between resistance change and strain is presented in Figure 2. In the elastic deformation stage (below 2%), the overall resistance of the APC-rGO / CNP sample gradually decreases, and the GF value calculated in the small strain rate region (ε<1.2%) is 1.065. Fig.12 e shows the relationship between the relative resistance change of APC-rGO / CNP and pressure. In the range of 0-1000 kPa, the overall resistance change rate of the APC-rGO / CNP sample decreases, and the calculated sensitivity is 0.22 kPa -1 Only when the pressure exceeds the compressive strength of the APC-rGO / CNP sample, the resistance signal will show a positive increasing trend. Fig.12f shows the resistance change of APC-rGO / CNP under different pressures in the first ten loading / unloading cycles. When the loading stress changes from 500kPa to 1000kPa, the waveform signal is negative, complete and regular. With the continuous increase of stress (≤3000kPa), the resistance change rate becomes positive, however, the signal peak of the resistance change shows a split peak and irregular shape. In order to further expand the application of APC-rGO / CNP in wearable electronic devices, its sensing performance in motion monitoring was studied. The APC-rGO / CNP sheet connected to the copper electrode was fixed on the finger to simulate the rapid movement mode, and the real-time resistance change law when pressing and releasing on the keyboard was monitored, as shown in Figure 2. Fig.12 In addition, the APC-rGO / CNP sensor was fixed on the hand to monitor the vibration feedback and duration when making and relaxing the fist ( Fig.12 h), this application can be transferred to rehabilitation training, which is very helpful for those who have tendon and joint damage and cannot move their hands flexibly. Therefore, the synergistic effect of the porous structure and graphene / carbon film can enhance the advantages of mechanical properties and conductivity of electrodes and sensors, showing the great application potential of APC-rGO / CNP porous carbon composites in energy storage and sensing devices.
[0106] The present invention develops a novel bread-derived hierarchical porous carbon material, which forms structural disorder caused by irregular carbon nanoparticles through a simple, low-cost and environmentally friendly method. -1 The specific capacitance at the current density is as high as 474.8Fg -1 , and exhibited an excellent conductivity of 3.23S cm -1 and a high compression modulus of 124.60 MPa. In addition, the assembled symmetric solid-state APC-rGO / CNP / / APC-rGO / CNP supercapacitor has a power density of 895 W kg -1 Its energy density is 17.4Wh·kg -1 , and the maximum power density is 4680Wkg -1 Under different loading conditions, the porous electrode structure and the changes in the electrode / electrolyte interface are conducive to accommodating a large amount of charge. Therefore, under a high compressive stress of 20 kPa, the specific capacitance of the supercapacitor is 227.8 F g -1 , when the power density is 822.8W kg -1 Its energy density is as high as 25.6W h kg -1 In addition, APC-rGO / CNP porous carbon materials can be used in multifunctional pressure sensor devices with an ultra-wide response range of 0-3000 kPa and a -1However, when the stress exceeds 3000 kPa, stress concentration and cracks are easily formed at the edges of the pore skeleton, resulting in damage to the internal structure of the material. These findings show the potential of bread-derived porous carbon composites as a multifunctional material for building advanced energy storage and sensing electronic devices.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing composite porous carbon, characterized in that: The preparation method of the composite porous carbon comprises the following steps: S1. Preparation of active porous carbon APC: S1.1, carbonizing the dried bread in argon at 600°C to obtain bread carbon material; S1.2, immerse 600 mg of bread carbon material in 50 mL of 1 mol / L KOH solution for 10 min, and then keep the bread carbon material sample treated with KOH in argon at 600 ° C for 1 hour to obtain APC material; S1.
3. Thoroughly wash the APC material with deionized water to remove residual chemicals; S2. Synthesis of APC-rGO and APC-rGO / CNP composites: S2.1, immersing the prepared APC block into 50 mL of 5 mg / mL graphene oxide GO dispersion; S2.2, keeping the APC coated with GO dispersion in a drying oven at 60° C. for 4 hours to obtain APC-GO; S2.3, synthesis of APC-rGO composite material: 100 mg of ascorbic acid was mixed in 50 mL of deionized water by stirring to obtain a mixed solution 1; then, the APC-GO material was immersed in the mixed solution 1 for 2 hours, and this process resulted in the reduction of APC-GO to obtain an APC-rGO composite material; S2.
4. Synthesis of APC-rGO / CNP composite material: APC-GO material was placed in a mixed solution II including 300 mg 1,4-phenylenediboronic acid and 20 mL methanol to obtain a mixture; then, the mixture was placed in a 50 mL Teflon reactor and the temperature was set to 90°C. After 24 hours, the mixture reacted on the APC surface to generate graphene oxide framework film APC-GOFs. Then, the APC-GOFs was washed with methanol several times; 100 mg ascorbic acid was mixed in 50 mL deionized water by stirring to obtain a mixed solution III; then, the APC-GOFs material was immersed in the mixed solution III for 2 hours. This process resulted in the reduction of APC-GOFs; finally, the APC-rGO / CNP composite material was obtained.
2. The method for preparing composite porous carbon according to claim 1, characterized in that: The bread in S1.1 is ordinary bread made from flour, and the bread is carbonized in argon for 3 hours.
3. The method for preparing composite porous carbon according to claim 2, characterized in that: The size of the APC block in S2.1 is 1 cm×1 cm×2 cm.
4. The method for preparing composite porous carbon according to claim 1, characterized in that: The APC-rGO / CNP composite material has a specific capacitance of 474.8 F / g, a conductivity of 3.23 S / cm, and a compression modulus of 124.60 MPa at a current density of 1.0 A / g.
5. The method for preparing composite porous carbon according to claim 4, characterized in that: The APC-rGO / CNP composite material is used to assemble a symmetrical solid-state APC-rGO / CNP / / APC-rGO / CNP supercapacitor with a power density of 895 W·kg -1 When the energy density is 17.4Wh·kg -1 , and the maximum power density is 4680Wkg -1 .